THE EFFECT OF ONLINE TRANSPORTATION CUSTOMER SERVICE QUALITY ON CUSTOMER LOYALTY IN BANDAR LAMPUNG - Kusuma, Desta Surya; Indriyani, Susi (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The convenience offered by online transportation applications has an impact on the choice of transportation to the community. Community mobility is faster and can shorten the time for activities. there are currently two online transportation operators in Indonesia, namely Grab and Gojek, both of which have advantages in offering online transportation services to the public. The phenomenon that occurs in online transportation services is that sometimes there is a sense of worry with unknown drivers or drivers who drive do not follow traffic rules. There are also different types of vehicles in the application with vehicles used by online transportation drivers. This is what underlies this research, which aims to find out how online transportation services to the loyalty of online transportation users in Lampung city, until this study amounted to 224 people. The results of this study show that reliability, physical evidence, level of response and empathy affect the loyalty of users of online transportation.Keyword: service; transportation; loyalty;